UNESCO Chair in Health Education: A Step toward Public Health Improvement - M Moin; N Rezaei; M Yeganeh (Tehran University of Medical Sciences, 2006)
The UNESCO Chair in Health Education in TUMS (TUMS), Iran, was established in Immunology, Asthma and Allergy Research Institute in April 2004. The purpose of this chair is to promote an integrated system of research, training, information and documentation activities in the field of health education. The target group includes the public, health care workers, students, trainees and researchers. During its one year existing, the Chair has supported financially eleven admitted proposals and supported technically eight submitted proposals in divers fields regarding health issues with the cooperation of other research institutes in TUMS. It has made connections with most of the national research institutes and universities to establish multi-centric collaborations. The activities of the Chair are being directed towards the health priorities of the country and region. The Chair has contributed to an important international congress on immunodeficiency disorders as well as another meeting on Asthma in near future. The Chair is to publish several educational books, booklets and CDs related to health education; it is also going to prepare a thorough proposal on HIV/AIDS prevention with collaboration of other institutions, which could be applicable regionally, and in neighboring countries and states.